Dust effect on optically stimulated luminescence dosimetry - (:unkn) unknown (RAD Association, 2017)
Optically stimulated luminescence dosimetry (OSLD) has been used for dose measurements in many different radiation fields for personal monitoring and medical and industrial applications. One of the most important advantages of the OSLD compared to thermoluminescence dosimetry (TLD) is the light source used to stimulate the crystal. On the other hand, there is a discrimination problem between the light used in a stimulation and the luminescence light obtained as a result of stimulation. To measure the correct dose value, the stimulation and luminescence light have to be discriminated precisely by using different optic filters such as UV blocking, long and short band filters. In addition, the OSL readers are calibrated under fixed conditions (normal operating condition of optic filters, light source, photomultiplier tube, etc). The measured dose values are very sensitive to changes in normal operating conditions. In this work, the dust buildup factor on the optic filters is studied to analyse the response of BeO OSL dosimeter system. The elemental composition of suspended dust was determined by using the literature given for samples obtained from different indoor locations in Turkey and abroad. The light transport algorithm is used to simulate BeO OSL dosimeter system’s response with and without dust buildup by means of Monte Carlo photon transport technique. The Coherent and incoherent scattering of the light, as well as other photon interaction mechanisms, were explicitly modelled in Monte Carlo simulations. The dust buildup effects on OSL spectrum were investigated in detail as a function of dust thickness on the optic filters and elemental composition of the dust. © RAD Conference Proceedings. All rights reserved.
Keywords: Dosimetry; Dust effect; Monte Carlo simulation; Optically Stimulated Luminescence Dosimetry (OSLD)